Sudden stop: Supply and demand shocks in the German natural gas market - Jochen Güntner; Magnus Reif; Maik H. Wolters (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
We use a structural VAR model to study the German natural gas market and investigate the impact of the 2022 Russian supply stop on the German economy. Combining conventional and narrative sign restrictions, we find that gas supply and demand shocks have large and persistent price effects, while output effects tend to be moderate. The 2022 natural gas price spike was driven by adverse supply shocks and positive storage demand shocks, as Germany filled its inventories before the winter. Counterfactual simulations of an embargo on natural gas imports from Russia indicate similar positive price and negative output effects compared to what we observe in the data.
Keywords: E32; F51; Q41; Q43; Q48; 330; Energy crisis; German natural gas market; narrative sign restrictions; natural gas price; structural scenario analysis; vector-autoregression